Zinc + nickel + microparticles coatings: production process and structural characterization - Mahmud, Zulema A. (2015)
The properties of coatings obtained from Ni-Zn electrodeposition baths containing microparticles is analyzed. The incorporation of alumina or silicon carbide microparticles improves properties of hardness and protection of the coating. The Ni content in the alloy, which normally varies between 10 and 15 %, was measured by X-ray fluorescence. ZnNi-particles coatings show a high nickel content and high corrosion resistance. The incorporation of uniformly distributed particles in the coatings is achieved under controlled conditions of current density and mechanical stirring. It was found that in the present case, 8 A/dm2 is the optimal electrodeposition current density. Frontal coatings samples were studied by scanning electron microscope while cross sectional area by optical microscope. The surface analysis was performed by energy dispersive X-rays spectroscopy microprobe and the structural characterization by X-ray diffraction. The last technique showed that the phase (3,3,0) is reinforced after 10 minutes of electrodeposition in the presence of CSi, while there is a change from ZnNi (3,3,0) to ZnNi (1,1,0) in the presence of Al2O3. This led to an increment of the compressive forces in the material. The charge transfer resistance (RTC) of the coating depended on its own thickness. High values of RTC corresponded to lower values of corrosion current J0. Experimental results showed that RTC10 microns> RTC 20 microns > RTC5 microns, indicating that the best properties of the material were obtained at 10 microns. In industrial scale process and in the laboratory, it was found that electrolyzing during 10 minutes with different J is: RTC(8 A dm-2) > RTC(10 A dm-2) > RTC(6 A dm-2). Zn-Ni-CSi coatings showed a decrease in the crystal size when saccharin is added to the electrodeposition solution.